Analysis of Diazo Quinolinone Complexes with Various Metal Ions - Rumengan, Stefan Marco; Ummah, Khoirotul; Mardliyah, Ana; Wijaya, Jefry; Tambalean, Febrindah Ester; Tengker, Soenandar Milian; Saiya, Abdon; Karundeng, Marlina; Paat, Vlagia Indira (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
Quinolones are heterocyclic compounds that are important in medicine and materials for DSSCs or OLEDs. One thing that is rarely studied is the ability to detect metal ions. Diazo groups have an important role in forming complexes with metal ions. This research aims to obtain initial information regarding the metal detection capabilities of diazo quinolinone compounds. The compound 7-[(2,4-dihydroxyphenyl)diazenyl]-4-methyl-2-quinolinone is the test target. Tests were carried out with various metal ions in MeOH. Next, the wavelength of the complex was determined using a UV-Vis spectrophotometer. The results of complex analysis of Compound 2 with various metal ions show the potential to be an indication of the presence of metal ions.